Pengujian Sistem Informasi Pelayanan Desa Terhadap Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Prasianto, Kornelius Reinand; Hartomo, Kristoko Dwi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Sirembukwarga.salatiga.go.id is a website for submitting a development budget in the village and obtaining direct approval from BAPPEDA (Regional Development Planning Agency) Salatiga city. The purpose of this study was to test the village service information system on user satisfaction. Therefore, it is necessary to test the quality of the sirembukwarga.salatiga.go.id website to find out the problems experienced by users to achieve user satisfaction. Based on the existing problems, namely the appearance of the website is unresponsive, has an unattractive appearance, is less efficient, difficult to use considering that users do not understand the use of technology, so that it is difficult to convey information for users, a Village Service Information System Test is needed using the WEBQUAL 4.0 method. The initial stage of this research by testing the website, collecting data using a questionnaire to the users. The selection of respondents using the Multi Stage Random Sampling method due to data collection for several villages in the city of Salatiga. The results of data collection using a questionnaire to determine the quality of the website. The data of this study obtained a sample of 40 respondents and processed using SPSS version 25. The results of the Usability Quality and Information Quality tests do not have good quality because user satisfaction has not been met. On the other hand, Interaction Quality has good quality. This test is conducted to find out how satisfied the users are in using the services provided by the government. The results of this study indicate that the three variables tested have an influence and impact of 68.9% and are influenced by factors outside the webqual dimension of 31.1%.